Blue Light Therapy in Dermatological Practice: A Review - Giuseppe Lodi; Fortunato Cassalia; Mario Sannino; Giovanni Cannarozzo; Adone Baroni; Simone Amato; Elena Zappia; Giovanni Pellacani; Steven Paul Nisticò (Cosmetics)
For some years, blue light at a wavelength of 400–500 nm has emerged as a non-invasive and innovative treatment in dermatology. This narrative review provides a comprehensive exploration of the mechanisms by which blue light exerts therapeutic effects on various skin disorders including treatment of acne vulgaris, psoriasis, atopic dermatitis, vitiligo, androgenetic alopecia, ulcers and photoaging. We delve into the antimicrobial properties of blue light, highlighting its ability to generate reactive oxygen species that target and destroy pathogenic microorganisms such as Cutibacterium acnes. Additionally, we examine its anti-inflammatory effects, which involve the modulation of cytokine production and reduction in inflammatory cell infiltration, contributing to symptom relief in chronic inflammatory conditions. Blue light, through interaction with some photoreceptors, belonging to the Opsin family, is able to stimulate and prolong the anagen phase in the hair’s life cycle and stimulate repigmentation in vitiligoid patches. The photobiomodulation properties of blue light are also discussed, emphasizing how it influences cellular activities like proliferation and differentiation, thereby aiding in skin rejuvenation and healing processes. By assessing the clinical efficacy, safety profiles, and potential adverse effects reported in the current literature, we aim to present a balanced perspective on the utility of blue light therapy. The review also discusses advancements in light-emitting diode (LED) technology that have enhanced treatment delivery and patient outcomes. Furthermore, we outline future directions for research and clinical applications, emphasizing the need for standardized treatment protocols and long-term safety studies to fully integrate blue light therapy into dermatological practice.